"I Am a Peacemaker": Writing as a Space for Recontextualizing Children's Identity in a Catholic First Communion Preparation Course. (July 2015) - Tusting, Karin
This article reports on research addressing the role of writing as a space for producing representations of children's identity as Catholics in a First Communion preparation course. It draws on data from ethnographic participant observation over one year in a Catholic parish in England, focusing on writing in the preparation sessions, taking a social practice approach to identity and literacy. The article argues that in this course, written texts are drawn on to provide spaces within which children produce written representations of aspects of their lives that reify their identities as Catholics. Analysis of the data set demonstrates four ways in which particular kinds of identities were constructed through writing processes. Writing provided space for reframing aspects of children's unique histories and identities within a faith-based perspective; representing children as active agents in the world; producing reifications of internal emotional states in linguistic form; and making relational connections between the children and their church, home, and friendship communities. The article argues that the production of these reframings of children's identities requires multiple kinds of recontextualizations, and that writing provides a key means by which these are brought together.